KAJIAN HUKUM PERLINDUNGAN KONSUMEN TERHADAP KONSUMEN YANG MENGGUNAKAN KARTU KREDIT - Rini T Simangunsong (JURNAL RECTUM: Tinjauan Yuridis Penanganan Tindak Pidana, 2023)
The dynamics of the development of an increasingly modern global society along with the development of its economy has also influenced the pattern of life of the people themselves. Credit cards as an aspect of modern society's life have become a means of payment in lieu of cash which is increasingly in demand by the public or consumers today, because they have their own prestige, and have even become a lifestyle trend in big cities. This is also supported by the many shopping centers that serve cashless payments. In Law Number 8 of 1999 Article 1 paragraph (1) concerning Consumer Protection, it states that "Consumer protection is all efforts that guarantee legal certainty to provide protection to consumers." The general objective of writing this thesis is to explain how to study consumer protection law for consumers who use credit cards. The increase the use of credit cards is certainly triggered many benefits that can experienced credit card holders, especially the ease of making transactions and security for consumers because they do not need to carry large amounts of cash. The approach to using a credit card is not only carried out in terms of economic needs, but must also be supported by a legal approach, so that it is recognized and applies in economic law relations. This type of research empirical legal research and the nature of research is descriptive qualitative and the data used are primary and secondary data.